You can't lie to me : the revolutionary program to supercharge your inner lie detector and get to the truth - Driver, Janine (HarperOne, 2012)
A "New York Times"--Bestselling author and lie detection expert for the ATF, FBI, and CIA uncovers the tools to recognize liars in this easy-to-follow program that will help readers lead a confident, trust-filled life